Potret pemahaman guru dan siswa terhadap hakikat ilmu pengetahuan alam di era pembelajaran abad ke-21 - Siti Nurkamilah; Wahyu Sopandi; Henni Riyani; Annisa Meristin; Anisanur Marwah (Universitas Sebelas Maret, 2025)
This research aims to analyze the level of understanding of elementary school teachers and students on the essence of Natural Sciences (IPA) in the 21st century learning era. The focus of the research is directed at the three main dimensions of the essence of science, namely scientific knowledge, scientific processes, and scientific attitudes, as well as their relationship with the level of interest in science. This study used a quantitative descriptive method with the population of all teachers and elementary school students in several schools in the research area. Sampling was carried out using purposive sampling techniques, involving a total of 88 teachers and 263 students from the upper classes of elementary schools in 4 provinces in Indonesia. The research instruments are in the form of a questionnaire on understanding the essence of science and an interest questionnaire on science, which has been validated by experts and tested for reliability using the Cronbach Alpha coefficient. The results of the study show that the level of understanding of teachers and students on the essence of science in general is in the medium category. Teachers show a good understanding of aspects of scientific attitudes, such as honesty, hard work, and scientific responsibility, but are still weak in understanding the tentative, subjective, and limited nature of science. There was also a difference in tendency based on gender, where male teachers had a slightly higher understanding of the essence of science than female teachers, while female students showed a better understanding than male students. In addition, interest in science has a positive effect on understanding the essence of science. These results confirm the importance of Nature of Science (NoS)-based learning and teacher training that are oriented towards strengthening science literacy as well as the development of contextual learning strategies to foster students' scientific interests and attitudes in a sustainable manner.